Suppression of segregation and control of the structure of ingots and casting - Shapovalov, V.O.; Grigorenko, G.M.; Nikitenko, Yu.O.; Yakusha, V.V.; Shapovalov, E.V. (Вопросы атомной науки и техники, 2020)
The problem of segregation in large ingots, which are used in energy, heavy engineering, etc., is considered. A new approach to suppressing segregation processes is proposed. It consists in regulating the local crystallization time by organizing a surfaced local metal bath on the surface and adjusting the speed of its movement, while an ingot is formed layer by layer. Розглянуто проблему ліквації в крупних злитках, які використовуються в енергетиці, важкому машинобудуванні тощо. Запропоновано новий підхід щодо пригнічення лікваційних процесів. Він полягає в регулюванні локального часу кристалізації шляхом організації на поверхні, що наплавляється, локальної металевої ванни і регулюванні швидкості її переміщення, при цьому злиток формується шар за шаром. Рассмотрена проблема ликвации в крупных слитках, которые используются в энергетике, тяжелом машиностроении и др. Предложен новый подход к подавлению ликвационных процессов. Он заключается в регулировании локального времени кристаллизации путем организации на поверхности наплавляемой локальной металлической ванны и регулировании скорости ее перемещения, при этом слиток формируется слой за слоем.